2021
DOI: 10.1590/1980-5373-mr-2020-0429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Niobium Addition on Microstructure and Machinability of High Chromium Cast Iron

Abstract: High Chromium Cast Iron (HCCI) is mostly utilised in environments under severe abrasion and corrosion wear conditions, and research on this material with added niobium obtained positive results regarding wear resistance. The casting process has surface finish and dimensional accuracy limitations compared to machining processes. There are too few studies about HCCI machinability and no one about HCCI with niobium additions. HCCI machinability studies may allow new applications for this material when excellent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Several studies 5,[10][11][12][13] showed that small concentrations (less than 1%) of Nb can have a beneficial effect on the wear resistance of HCCI 6 . Furthermore, recent authors have shown that 0.5%Nb in HCCI addition can increase the material machinability at rates over 100% in some conditions 9,14 , encouraging interest in this range.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies 5,[10][11][12][13] showed that small concentrations (less than 1%) of Nb can have a beneficial effect on the wear resistance of HCCI 6 . Furthermore, recent authors have shown that 0.5%Nb in HCCI addition can increase the material machinability at rates over 100% in some conditions 9,14 , encouraging interest in this range.…”
Section: Introductionmentioning
confidence: 97%
“…The wear mechanisms associated with tool wear are categorized into abrasion, oxidation, attrition, and diffusion. A comprehensive analysis of wear mechanisms is very important for interpreting behavior and understanding the dynamic interaction between the tool and the chip [11].…”
Section: Introductionmentioning
confidence: 99%